Adoption of postharvest innovations to minimize tomato losses in Nigeria - Mesay Yami; Lenis Saweda O. Liverpool-Tasie; Ibukun Olaoye; Tesfamicheal Wossen; Shiferaw Feleke; Tahirou Abdoulaye (Scientific Reports)
Abstract Postharvest loss (PHL) remains a critical challenge in sub-Saharan Africa, particularly in Nigeria, where it exacerbates food insecurity and economic vulnerabilities. This study investigates the adoption of postharvest packaging technologies (PHPTs), focusing on reusable plastic crates (RPCs) for tomato harvesting and marketing, and examines farmers’ adoption decisions with market channel choices. Using a dataset of 1,704 tomato farmers, we address the potential endogeneity between RPCs adoption and the choice of market channels through a recursive bivariate probit model. The findings indicate that farmers engaged in long-distance sales are more likely to adopt RPCs, motivated by the potential for higher price premiums and reduced losses during transit. However, there are significant barriers to RPCs’ adoption, including high acquisition costs and limited availability in rural areas. The study findings also underscore the importance of irrigation practices, membership in farmers’ associations, and proximity to major output markets as key drivers of RPCs’ uptake. These insights are critical for informing targeted interventions to improve access to and adoption of PHPTs, thereby reducing PHL and strengthening the resilience of smallholder tomato farmers in Nigeria.